The Ethanolic Leaf Extract of Alchornea cordifolia (Schum. & Thonn.) Muell. Arg Inhibits the Development of Dyslipidaemia and Hyperglycaemia in Dexamethasone-Induced Diabetic Rats - Ama Kyeraa Thomford, Kwesi Prah Thomford, Fred Ayertey, Dominic Adotei Edoh, Kobena Amissah Thomford, Elvis O. Ameyaw, J. N. Boampong, M. Enimil, S. A. Bioh (Journal of Applied Pharmaceutical Science, 2015)
Poor lipid and glucose regulation increases the risk for the development of major cardiovascular diseases and other organ damage. The study evaluated the serum glucose and lipid lowering effects of the 70% (v/v) ethanolic leaf extract of Alchornea cordifolia (ALC) using the dexamethasone-induced diabetic rat model. Thirty six female Sprague-Dawley rats (180-200g; n=6) were rendered hyperglycaemic with dexamethasone (10 mg/kg, sc) once daily for 8 days except the normal control. Each group received either normal saline 0.5 ml/rat, ALC (250 mg/kg, p.o. or 500 mg/kg, p.o.), glibenclamide (5 mg/kg, p.o.) or atorvastatin (5mg/kg, p.o.) as treatment once daily for 8 days. Fasting blood glucose (FBS) readings were recorded at baseline, day 4, 6 and 9. Blood was collected for the estimation of serum triglycerides (TG), total cholesterol (TC), low density lipoproteins (LDL), very low density lipoproteins (VLDL) and high density lipoprotein (HDL) on day 9. The diabetic control group had significantly raised FBS levels (8.20 ± 1.04 mmol/l; ***p
Keywords: Alchornea cordifolia, antidiabetic, antihyperglycaemic, antihyperlipidaemic, herbal medicines.